Armed Forces as Security Agency and The Competence of Military Courts: The Prospect of Democratic Breakdown - Rodrigo Grazinoli Garrido; Ana Morell; Silvana Vieira Azevedo (Revista Brasileira de Direito Processual Penal, 2018)
This paper sought to discuss the role of the Armed Forces in Public Security, shedding light mainly on two points: the increased number of military crimes, especially those under Law nº 13.4891/17, and the maintenance of jurisdiction in military courts over conflicting parties involved in lawsuits of Law and Order Assurance nature. Therefore, an exploratory and qualitative research was developed based on national and international doctrine and jurisprudence, as well as on the Brazilian legislation. This enabled us to acknowledge that the way and the extent to which the Armed Forces have been employed in Public Safety and in the Brazilian criminal prosecution may result in great risks of damage to human rights and, hence, to democracy.